Sequential Electrodeposition of Bifunctional Catalytically Active Structures in MoO3/Ni–NiO Composite Electrocatalysts for Selective Hydrogen and Oxygen Evolution. Issue 39 (19th August 2020) - Li, Xiaopeng; Wang, Yang; Wang, Jiajun; Da, Yumin; Zhang, Jinfeng; Li, Lanlan; Zhong, Cheng; Deng, Yida; Han, Xiaopeng; Hu, Wenbin
Abstract: Exploring earth‐abundant and highly efficient electrocatalysts is critical for further development of water electrolyzer systems. Integrating bifunctional catalytically active sites into one multi‐component might greatly improve the overall water‐splitting performance. In this work, amorphous NiO nanosheets coupled with ultrafine Ni and MoO3 nanoparticles (MoO3 /Ni–NiO), which contains two heterostructures (i.e., Ni–NiO and MoO3 –NiO), is fabricated via a novel sequential electrodeposition strategy. The as‐synthesized MoO3 /Ni–NiO composite exhibits superior electrocatalytic properties, affording low overpotentials of 62 mV at 10 mA cm −2 and 347 mV at 100 mA cm −2 for catalyzing the hydrogen and the oxygen evolution reaction (HER/OER), respectively. Moreover, the MoO3 /Ni–NiO hybrid enables the overall alkaline water‐splitting at a low cell voltage of 1.55 V to achieve 10 mA cm −2 with outstanding catalytic durability, significantly outperforming the noble‐metal catalysts and many materials previously reported. Experimental and theoretical investigations collectively demonstrate the generated Ni–NiO and MoO3 –NiO heterostructures significantly reduce the energetic barrier and act as catalytically active centers for selective HER and OER, synergistically accelerating the overall water‐splitting process. This work helps to fundamentally understand the heterostructure‐dependent mechanism, providing guidance for the rational design and oriented construction of hybrid nanomaterials for diverse catalytic processes. Abstract : A new MoO3 /Ni–NiO hybrid electrocatalyst is designed and synthesized via a novel sequential electrodeposition strategy, which exhibits excellent activity and durability for the overall water splitting process. Experimental and theoretical analysis demonstrate the improved hydrogen evolution performance should be mainly attributed to the Ni–NiO heterostructure, and the generated MoO3 –NiO heterointerface is responsible for enhancing the oxygen evolution activity, synergistically facilitating bifunctional electrocatalysis.